Improving the Ability to Compare Content of Various Reviews to Find a Systematic Review Using the Problem Based Learning Model Private Vocational School 1 Mamuju - Ansar Ansar; Rahmat Hidayat; Syahban Mada Ali (Edumaspul: Jurnal Pendidikan, 2022)
This study aimed to determine the Increased Ability to Compare the Content of Various Reviews to Find the Systematics of a Review Using the Problem Based Learning Model. The population in this study were all students of class XI at SMK Negeri 1 Mamuju. The data consisted of data on student learning outcomes through learning achievement tests in each cycle and data on student activities in learning based on observations made. Student learning outcomes test data were analyzed using the mean while student learning activity data were analyzed using descriptive analysis. The results showed that the ability to compare the contents of various reviews to find the systematics of a reviewer increased in each cycle. Based on data on pre-cycle, there is 1 student who is in the complete category with a score of 75 and above with a percentage of 4%, cycle I 15 students who are in the complete category with a percentage of 60%, cycle II 18 students who are in the complete category with a percentage of 72% and cycle III 25 students in the complete category with a percentage of 100%. Based on the results of the data analysis, it was concluded that the use of the Problem Based Learning model could improve the ability to compare the contents of various reviews to find the systematics of class XI student reviews at SMK Negeri 1 Mamuju.